Relationship between Need for Achievement and Interest in Entrepreneurship for the students of the Sharia Business Management Study Program at UIN Sayyid Ali Rahmatullah Tulungagung - Hima Widyas Asmara (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to determine the relationship between need for achievement and entrepreneurial interest in students majoring in Islamic Business Management.State Islamic University of Sayyid Ali Rahmatullah Tulungagung. The hypothesis proposed in this study is that there is a positive relationship between need for achievement and entrepreneurial interest. The higher the need for achievement, the higher a person's entrepreneurial interest. And conversely, the lower the need for achievement, the lower a person's entrepreneurial interest. The subjects in this study were 70 students. This study used quantitative research, and data were collected using a questionnaire on need for achievement and interest with a Likert scale. Analyzed the data using SPSS 18.0 for windows. The results of the correlation analysis using the Pearsons Product Moment Correlation technique obtained a positive relationship. So the initial hypothesis is accepted, there is a positive relationship, the higher the need for achievement, the higher the entrepreneurial interest. Students who have a high need for achievement will be creative and innovative in completing tasks accompanied by the responsibility to pay attention to time so that they are fast and efficient in completing each task.Positive relationship between Need for Achievement and entrepreneurial interest of students majoring in Islamic Business Management. From these results, it can be seen that students who have a high need for achievement will have a sense of enthusiasm and ambition, and have confidence in their abilities